The Impact of Deep Learning-Based Chatbot Intervention on Students' Cognitive Load and Narrative Writing Literacy in Indonesian Language Learning at SD 030 Bagan Jaya (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aims to analyze the effect of a deep learning-based chatbot intervention on narrative writing literacy and cognitive load among elementary school students. Specifically, the study focuses on how the use of the chatbot can enhance student engagement in the writing process, support the development of critical thinking skills, and reduce affective and cognitive barriers during learning. Research Method: This study employed a quasi-experimental design with a Pretest–Posttest Control Group approach. The sample consisted of 40 fourth-grade students from SD 030 Bagan Jaya, divided into an experimental group receiving the chatbot intervention and a control group receiving conventional writing instruction. Data were collected through narrative writing literacy tests and a cognitive load assessment rubric. Data analysis was conducted using an independent t-test to determine the effect of the intervention on both research variables. Research Findings: The results indicated that the experimental group experienced a significant improvement in narrative writing literacy and a reduction in cognitive load compared to the control group. The posttest mean scores for writing literacy increased substantially, while the standard deviation decreased, indicating more consistent student performance. The chatbot functioned as a digital tutor providing adaptive scaffolding, real-time feedback, and guidance that facilitated idea generation, text structuring, and revision skills. This intervention also enhanced student motivation and engagement, creating a safe and interactive learning environment. Novelty: This study emphasizes that the use of deep learning-based chatbots is not only relevant for secondary education but also effective at the elementary level. The findings contribute new insights by demonstrating that integrating AI into narrative writing instruction can serve as an innovative pedagogical strategy that simultaneously supports literacy development, critical thinking skills, and student motivation.